2020
DOI: 10.1016/j.scitotenv.2020.139281
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic persuaded lockdown effects on environment over stone quarrying and crushing areas

Abstract: Particulate matter concentration by three to four times amid lockdown.• Surface temperature is reduced by 3-5°C.• Amid lockdown noise level is reduced from 85dBA to b65dBA. • Total dissolve solid concentration in river water is reduced by two times.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
147
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(169 citation statements)
references
References 51 publications
10
147
0
12
Order By: Relevance
“…[15,12] have already reported that the high accumulation of greenhouse gases may lead to surging temperatures and may also affect other climatic components like fog, dew, precipitation etc. [13] have also reported reduction in temperature values by 3-5 °c as compared to pre-lockdown period in middle catchment of Dwarka river basin of Eastern India due to reduction in industry and vehicular movement induced energy footprints.…”
Section: Ambient Temperature (At) (°C)mentioning
confidence: 94%
See 1 more Smart Citation
“…[15,12] have already reported that the high accumulation of greenhouse gases may lead to surging temperatures and may also affect other climatic components like fog, dew, precipitation etc. [13] have also reported reduction in temperature values by 3-5 °c as compared to pre-lockdown period in middle catchment of Dwarka river basin of Eastern India due to reduction in industry and vehicular movement induced energy footprints.…”
Section: Ambient Temperature (At) (°C)mentioning
confidence: 94%
“…In addition to above, changes in the economic output, decreased energy consumption, reduced emissions from land usage, livestock, septic processes and application of synthetic fertilizers due to lockdown might have resulted in lower atmospheric temperature than 2019; thus lowering risk of threat to our environment [11,12]. Also, the concentration of pollutants such as NO 2 , SO 2 , CO, Particulate Matter is considered as dominant reason of increase in air temperature [13] but lack of anthropogenic activities might have resulted in lesser emissions resulting in lower temperature values. In another study [14], there was also depiction of a positive correlation between air quality parameters and weather parameters.…”
Section: Ambient Temperature (At) (°C)mentioning
confidence: 99%
“…Moreover, studies suggest that more developed countries could be more substantially influenced by lockdown, as industrial activities remain largely suspended (16). Similarly, the lockdown effects are larger in rich and cold areas and cities with more traffic volumes experience a more substantial reduction in air pollution because richer countries have higher electricity demands and colder areas have higher coal demands, respectively (29)(30)(31)(32)(33). Data like these hint that mother earth is an unintended beneficiary of the Covid-19 pandemic.…”
Section: Decrease In Air Pollution Levelmentioning
confidence: 99%
“…As mentioned, the locking down of cities has significantly improved the environmental quality with a sharp drop in air pollution levels across several countries (2,6,(29)(30)(31)(32)(33). Whereas, before and after lockdown comparison is problematic because it lacks proper counter facts.…”
Section: Decrease In Air Pollution Levelmentioning
confidence: 99%
See 1 more Smart Citation